Breath by breath - Unveiling Early Small Airway Changes with Novel Diagnostics - Nasr, Abir (Lund University, Faculty of Medicine Doctoral Dissertation Series, 2025)
Chronic obstructive pulmonary disease (COPD) and asthma both involve inflammation and structural changes in the peripheral airways that are not detectable with current standard tools such as spirometry. Accurate and sensitive assessment of lung function is crucial for early diagnosis, monitoring disease progression, and guiding appropriate treatment. The overall aim of this thesis was to investigate alternative and less explored methods for detecting early or subtle dysfunction in small airway physiology in individuals with COPD, asthma, and healthy smokers, and to compare their diagnostic value with established pulmonary function tests (PFTs). In Papers I and II, more sophisticated measures of respiratory oscillometry were investigated in different settings in COPD and asthma. Paper III evaluated comprehensive PFTs, including respiratory oscillometry, in never-smokers with COPD. Paper IV explored the severity of airway obstruction and preserved lung function assessed by ventilation/perfusion (V/P) SPECT in young and older healthy smokers and subjects with COPD. In Paper I, within-breath measures of respiratory oscillometry, reflecting expiratory flow limitation, were most prominent in parameters measuring peripheral resistance and reactance. Paper II demonstrated that higher baseline inspiratory resistance, primarily reflecting peripheral airways, was an indicator of a positive mannitol challenge test in asthma. Paper III provided further evidence that COPD in never-smokers presents with mild pathophysiological changes and constitutes a distinct phenotype affecting the small airways. Paper IV identified increased ventilation impairment in a subgroup of young healthy smokers despite normal spirometry. In the older cohort, most variables indicated impaired lung function, with higher obstruction grades observed in the COPD group. In conclusion, respiratory oscillometry is a promising technique for assessing peripheral airway function, and its clinical utility should be further explored alongside conventional methods. V/P SPECT is a sensitive imaging modality that can detect ventilation heterogeneities earlier in the disease process than standard lung function tests.
Keywords: peripheral airways; COPD; Asthma; Respiratory oscillometry; Resistance; Reactance; V/P SPECT; symptoms